Validation and application of three-dimensional auralisation during concert hall renovation. Issue 4 (December 2020) - Tronchin, Lamberto; Merli, Francesca; Manfren, Massimiliano; Nastasi, Benedetto
During the renovation of auditoria and concert halls, the acoustic quality is normally evaluated from measurements of impulse responses. One possibility for evaluating the acoustic quality from the measurements (the simulations) consists of convolving anechoic music with the measured (or simulated) impulse responses. In this way, a psycho-acoustic test is achieved using a virtual sound field representation. The listening room 'Arlecchino' at the University of Bologna includes ambisonics (up to fifth order) and stereo-dipole playback for virtual reproduction of sound in rooms. In this article, the effectiveness of the listening room 'Arlecchino' is first analysed, comparing acoustic parameters obtained from binaural impulse responses measured in some opera houses (in Italy) and auditorium (in Japan) with those virtually measured after the virtual reconstruction obtained in the listening rooms. The similarity between real and virtual sound fields, has been evaluated by comparing different acoustic parameters calculated by real and virtual sound fields, in four halls in different configurations, by means of the stereo-dipole method. In the second part of the article, the listening room was used to analyse the variation in interaural cross-correlation measurements in rooms obtained considering different anechoic sound signals convolved with the binaural impulse responses, to quantify the variation of the interaural cross correlation with different motifs. For this purpose, two different musical instrument digital interface musical motifs, very different from each other for their music characteristics, have been considered. Moreover, for each musical motif, different sound characteristics (i.e. different musical instruments) were considered, to consider both the rhythmic and timbre aspect.